Anatomicosurgical segmentectomy of the left ventricle for systematized partial resection of the heart: an experimental study - DI DIO,Liberato John Alphonse (1998)
A surgical experimental investigation is being carried out in an attempt to provide a viable alternative to the current approaches to cardiac resection of the left ventricular myocardium in cases of cardiomyopathies with dilated ventricle. The experiments are based upon the presence of anatomicosurgical segments in the dog's heart similar to those existing in the atria and ventricles of humans. So far three mongrel dogs (weight 15 kg) were submitted to cardiac catheterism to evaluate the anatomy of the coronary arteries and their branches, the function and cavity of the left ventricle (LV). A lateral thoracotomy on the left side was performed to expose the heart. Cardiopulmonary bypass (CPB) of each animal was established through the right atrium and the femoral artery (4 mg/kg Heparin, at 32°C, intermittent aorta cross-clamping). The left marginal artery and veins were ligated, causing an area of acute myocardial infarction, showing well-defined sharp limits. Such an area was then resected and the left ventricle was reconstructed. The animals were weaned from CPB, one dog having remained in a stable condition during a 7-day period of observation. The second was sacrificed after 4-day period of observation and the third dog died four hours after CPB owing to an excessive reduction of the LV chamber related to an anatomical variation. Pre and post operation transthoracic echocardiograms were obtained after undergoing cardiac catheterism. The echocardiogram revealed discrete mitral insufficiency, reduction of the diameter of the left ventricle with approximation of the papillary muscles, a dysfunction and an impressive reduction of the cavity of the left ventricle. Peri-sutural areas of infarction were not observed. The orientation given by the anatomicosurgical segmentation of the coronary circulation is an important alternative to the present surgical treatment of cardiomyopathies with dilated ventricle.